The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/00958972.2018.1503653
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural features of copper(II) complexes of N,N,N′,N′-tetramethylethylenediamine with 2-chlorobenzoate1− and 2-hydroxybenzoate1−

Abstract: Two copper(II) coordination complexes, formulated as [Cu(tmen)(ClBA)2] (1) and [Cu(tmen)(Hsal)2.H2O] (2), (where tmen = N,N,N′,N′-tetramethylethylenediamine (C6H16N2), ClBA = 2-chlorobenzoate (C7H4ClO2 1-) and Hsal 1-(C7H5O3 1-) = monoanion of o-hydroxybenzoic acid (salicylic acid), have been synthesized and characterized by elemental combustion analysis, spectroscopic techniques, thermal studies and single crystal X-ray analyses. The complex (1) consists of two distinct monomeric units in which coordination e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…There are a lot of drinking and irrigation springs in Gallaorol district of Jizzakh region. The water of some springs is 10-15 liters per second, and most of them have healing properties, it has been proved by the results of our research [9]. In order to properly use some springs in Gallaorol district, the study of the hydrogeological conditions of the spring areas [10], the processes of spring formation, the composition of water and the amount of water released is considered to have an important scientific and practical nature.…”
Section: Introductionmentioning
confidence: 59%
“…There are a lot of drinking and irrigation springs in Gallaorol district of Jizzakh region. The water of some springs is 10-15 liters per second, and most of them have healing properties, it has been proved by the results of our research [9]. In order to properly use some springs in Gallaorol district, the study of the hydrogeological conditions of the spring areas [10], the processes of spring formation, the composition of water and the amount of water released is considered to have an important scientific and practical nature.…”
Section: Introductionmentioning
confidence: 59%
“…This shift can be accounted for the participation of oxygen of amide group in the complexes. TMEDA ligand has characteristic peak at 1214 cm −1 corresponding to υ(C−N) [25] . The peaks of stretching vibrations of R−N−(CH 3 ) 2 and C−N of TMEDA ligand were changed and shifted to lower and higher values and were appeared at 1401–1417 cm −1 (1413 cm −1 in the free TMEDA) and 1193–1225 cm −1 (1214 cm −1 in the free TMEDA) in the IR spectra for all complexes.…”
Section: Resultsmentioning
confidence: 99%
“…TMEDA ligand has characteristic peak at 1214 cm À 1 corresponding to υ(CÀ N). [25] The peaks of stretching vibrations of RÀ NÀ -(CH 3 ) 2 and CÀ N of TMEDA ligand were changed and shifted to lower and higher values and were appeared at 1401-1417 cm À 1 (1413 cm À 1 in the free TMEDA) and 1193-1225 cm À 1 (1214 cm À 1 in the free TMEDA) in the IR spectra for all complexes. This shift in peak position was accounted to the coordination of nitrogen atom of TMEDA to the metal ions.…”
Section: Ir Spectra Studies Of Ternary Complexesmentioning
confidence: 90%
“…The rest of the strains, B. spizizenii, K. pneumonia, and S. aureus, and the fungal strain A. niger showed no activity. For comparison, the authors [16] references to their previous works [17][18][19], in which study of copper(II)-Tmen-carboxylates complexes. In general, it can be concluded that coordination polymer 6b is significantly inferior to mononuclear analogs (for example, 6a) in antimicrobial activity.…”
Section: N-donor Ligandsmentioning
confidence: 99%